Integrating ethical considerations into digital business strategy: a mini systematic literature review - Astadi Pangarso; Heru Nugroho; Wardani Muhamad; Robbi Hendriyanto; Ade Gafar Abdullah (Faculty of Economics and Business, University of Muhammadiyah Malang, 2026)
The principle of